The relationship between the expression of serum asprosin and miR-21 in patients with osteoporosis and delayed healing after OVCF surgery - Gaoming Song; Silong Lin; Xianqi Zhang; Hong Pan (Journal of Orthopaedic Surgery)
Objective: To explore the relationship between serum asprosin, microRNA-21 (miR-21) expression, and delayed healing after surgery in patients with osteoporotic vertebral compression fractures (OVCF), and to construct a nomogram model. Methods: A prospective study inducted 300 OVCF patients treated with percutaneous vertebroplasty (PVP) from June 2022 to June 2024. Serum asprosin and miR-21 were measured preoperatively, and fracture healing was assessed via X-ray 3 months post-surgery. Patients were categorized into delayed healing and normal healing groups based on outcomes. The least absolute shrinkage and selection algorithm (LASSO) regression identified factors influencing delayed healing, followed by binary logistic regression analysis. A nomogram model was constructed to predict delayed healing, and its predictive value was evaluated using the receiver operating curve (ROC) analysis. Results: Results showed higher rates of delayed weight-bearing (58.11% vs 33.19%), diabetes prevalence (52.70% vs 42.48%), bone cement injection volume (4.68 ± 1.14 mL vs 3.81 ± 1.09 mL), and serum asprosin levels (4.09 ± 1.39 ng/mL vs 3.14 ± 1.07 ng/mL) in the delayed healing group compared to the normal healing group. Serum miR-21 levels were lower in the delayed healing group (0.69 ± 0.19) than in the normal group (0.92 ± 0.31) ( p < 0.05). Bone density T scores in OVCF patients correlated positively with asprosin (r = 0.281, p < 0.001) and negatively with miR-21 (r = −0.184, p = 0.001). The LASSO regression identified five factors associated with delayed healing: bone cement volume, delayed weight-bearing, diabetes, and serum asprosin (risk factors), while high miR-21 was protective. Logistic regression indicated significant risk factors with an overall C-index of 0.867 and AUC of 0.868 (sensitivity 0.892, specificity 0.686). After 3 months of treatment, serum Asprosin [(3.46 ± 1.22) ng/ml] in OVCF patients was lower than that before treatment [(3.03 ± 1.03) ng/ml], and serum miR-21 (0.85 ± 0.30) was higher than that before treatment [(0.99 ± 0.33)] ( t = 4.039, 4.318, p < 0.05). Conclusion: Serum asprosin and miR-21 levels are closely related to delayed healing after surgery in patients with OVCF. Additionally, the bone cement injection volume, delayed weight-bearing, and concomitant diabetes mellitus are also important factors affecting fracture healing in patients. The nomogram model based on these factors can effectively predict the risk of delayed healing in patients with OVCF after surgery.